2009
DOI: 10.1021/jp901983j
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Amino Groups in Postsynthetically Modified Mesoporous Silica

Abstract: The accessibility of amino groups in postsynthetically functionalized mesoporous silica MCM-41, MCM-48, and SBA-15 is investigated by reaction with fluorescein isothiocyanate (FITC). The quantitative analysis of the surface-grafted amino groups in relation to the amount of coupled FITC over a wide range of loadings affords information about potential pore blocking. In the pore diameter domain of 3−4 nm, the actual pore size of materials with a one-dimensional channel system (MCM-41) strongly affects the FITC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…This method offers a wide range of chances to allocate diverse functional groups in MSNPs and also allows to chemically attach delicate organic functions prone to hydrolysis and elimination reactions [75]. One of the major issues of postsynthesis method is the possible blocking of the mesopore openings by the functional groups, which would lead unavoidably to heterogeneous functionalization of the mesoporous matrix [76]. Last, the surfactant displacement method consists in the direct surface silylation with simultaneous surfactant removal by using acidic alcohol as solvent [77,78].…”
Section: Their Applications As Drug Delivery Systemsmentioning
confidence: 99%
“…This method offers a wide range of chances to allocate diverse functional groups in MSNPs and also allows to chemically attach delicate organic functions prone to hydrolysis and elimination reactions [75]. One of the major issues of postsynthesis method is the possible blocking of the mesopore openings by the functional groups, which would lead unavoidably to heterogeneous functionalization of the mesoporous matrix [76]. Last, the surfactant displacement method consists in the direct surface silylation with simultaneous surfactant removal by using acidic alcohol as solvent [77,78].…”
Section: Their Applications As Drug Delivery Systemsmentioning
confidence: 99%
“…The degree of isolation of grafted groups such as amines can be probed by spectroscopic methods. 108,[111][112][113] Immobilizing multiple functional groups in MSN produces catalysts with advanced properties. Lin and co-workers 75 demonstrated that the simultaneous introduction of general acids and bases in the surface of MSN by co-condensation can lead to the efficient catalysis of a variety of carbon-carbon bond forming reactions.…”
mentioning
confidence: 99%
“…As a consequence of the shorter channels, the overall accessibility of the pore surface sites is much higher in nanometer-sized particles than in micrometer-sized particles having the same pore diameter. 48 For mesoporous silica nanoparticles, a sequential co-condensation approach has been proposed as an alternative to postsynthetic routes. It has been shown that functional groups can be concentrated in parts of the mesopores, or exclusively placed on the external surface, by adding the respective functionalized triethoxysilane during a specific time of the particle growth.…”
mentioning
confidence: 99%
“…51 There is evidence for the preferential adsorption of APTMS in the intrawall micropores of SBA-15. 48 In fact, micropores in SBA-15 can be functionalized independently from the primary mesopores by first cleaving and removing the accessible part of the SDA, thus exposing the mesopore surface. The latter is then functionalized and the material is heated to vacate the micropores.…”
mentioning
confidence: 99%